Modern Methods of Physical Adornment: In the Light of Islamic Teachings and Jurisprudential Interpretations - Dr. Abdul Rahman; Javed Iqbal (Journal of Religion and Society, 2025)
Islam is a comprehensive and all-encompassing religion that provides guidance for every aspect of human life, both individual and collective. It is not limited to worship or spiritual matters alone; rather, it offers complete and balanced directives in every field of human activity be it beliefs, ethics, social relations, economics, law, or culture. The human inclination toward beauty and physical adornment is a natural instinct, and this desire is not confined to women or any particular group or class; rather, it exists within the emotions of every individual. Islam acknowledges this natural tendency and not only permits adornment and cleanliness but considers them desirable. The blessed Sunnah of the Prophet Muhammad ﷺ contains numerous teachings and encouragements regarding bodily cleanliness, clothing, fragrance, grooming of hair, and enhancing facial appearance. The Prophet ﷺ said, “Indeed, Allah is beautiful and loves beauty” (Sahih Muslim). Thus, Islam accords importance to outward beauty but emphasizes its moral, religious, and natural dimensions as well, so that a person does not transgress the bounds of nature or fall into pride, ostentation, extravagance, or imitation of others.In the modern age, the field of physical adornment has witnessed extraordinary advancements. Numerous methods are now common, including cosmetic surgery, Botox, fillers, hair transplants, tattoos, nail art, skin bleaching, and even gender reassignment procedures. Behind these practices lie not only personal preferences or medical reasons, but also the influence of social media, societal expectations, cultural pressures, and aesthetic standards. Although some of these methods may appear harmless on the surface, they often involve intellectual, social, and religious complexities that can conflict with Islamic principles. Islamic jurisprudence evaluates these modern trends not merely from the perspective of physical adornment but in light of their legal permissibility, ethical justification, natural balance, and social implications. In some cases, these methods fall under prohibited categories such as taghyīr khalq Allāh (alteration of God's creation), tashabbuh bil-kuffār (imitation of non-believers), isrāf (extravagance), and unnatural exposure or display.Therefore, in this study, we will critically and analytically examine these modern methods of physical adornment in the light of Islamic teachings and juristic principles. The views of the four major schools of thought, contemporary jurists, and international Islamic jurisprudential bodies will be explored to clarify which methods are permissible, which are prohibited, and which may be conditionally allowed within certain Shariah boundaries. The objective of this study is also to determine to what extent contemporary Muslim men and women can benefit from these modern methods of beautification while remaining within the Islamic framework ensuring a balance between religious, ethical, and aesthetic values and protecting Muslim society from the onslaught of un-Islamic cultural invasions. Keywords: Modern Methods, Physical Adornment, Jurisprudential, Interpretations, Comprehensive, Encouragements, Islamic Framework, Social Relations